FACTORS ASSOCIATED WITH THE OUTCOME OF PERCUTANEOUS CORONARY INTERVENTION AFTER 6 MONTHS IN PATIENTS ≥75 YEARS OLD WITH ST-ELEVATION MYOCARDIAL INFARCTION (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate factors associated with the outcomes of percutaneous coronary intervention (PCI) after 6 months in patients aged ≥75 years with ST-elevation myocardial infarction (STEMI).Subjects and Methods: A prospective, interventional, cross-sectional study was conducted on 104 patients aged ≥75 years, diagnosed with acute STEMI and indicated for PCI at Vietnam National Heart Institute – Bach Mai Hospital, Hanoi Heart Hospital, and Huu Nghi Hospital during the period 2018–2023.Results: The incidence of major adverse cardiovascular events (MACE) at 6 months post-PCI was 18.3%. The risk factors significantly associated with MACE were: age ≥85 years (OR = 5.39; p = 0.020), diabetes mellitus (OR = 2.95; p = 0.037), Killip class III+IV (OR = 4.44; p = 0.011), TIMI risk score >6 (OR = 3.84; p = 0.019), CK-MB >39 (OR=3.35, p = 0.019), TroponinT T>4084.2 ng/L (OR = 8.02, p6), lower CK-MB concentration, Troponin T concentration, ST elevation ≥4.0 mm, triple-vessel coronary artery disease, and LMCA involvement.